Supporting Japanese Student’s Confidence and English Fluency through Formative Assessment - James Steven Herbach; Kinsella Valies (Journal of Linguistics and Language Teaching)
This classroom-based project included the development of clear and concise instructions, an analytic rubric as well as practice and testing materials to assess students’ speaking abilities. The speaking tasks consisted of three parts: reading aloud, describing a picture, and giving an opinion. As an extension of an ongoing departmental project originally focusing on second-year pharmacy students, the researchers have incorporated eleven first-year student groups from all departments. Six of the groups were offered the module face-to-face, while the other five received instruction, practice tasks, and feedback online.